Guidelines for Developing Learning Management Skills in the 21st Century for Teachers in Educational Institutions Under the Wang Chao District Group Tak Primary Educational Service Area Office 1 - Jantawong , Chayun; Yuttawong, Nontawat (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to: investigate the level of 21st-century learning management skills of teachers in schools under Wang Chao District Group, Tak Primary Educational Service Area Offices 1 and 2; and propose guidelines for developing 21st-century learning management skills of teachers in schools under Wang Chao District Group, Tak Primary Educational Service Area Office 1. The population consisted of 113 teachers and educational personnel, while the qualitative data sources included 11 experts, yielding a total of 124 participants in the 2024 academic year. The research instruments were questionnaires and interview forms. Quantitative data were analyzed using percentage, mean, and standard deviation, whereas qualitative data were analyzed through content analysis. The findings revealed that: 1. the overall and individual dimensions of teachers’ 21st century learning management skills were at the highest level. When ranked by mean scores, the highest dimension was information and communication technology (ICT) skills, followed by life and career skills, classroom management skills, and professional learning community (PLC) skills, respectively. 2. The guidelines for developing teachers’ 21st century learning management skills comprised four dimensions: (1) classroom management skills-teachers should utilize students’ background and behavioral data to design personalized learning using assessment tools and online platforms; (2) professional learning community (PLC) skills-teachers should actively participate in setting PLC goals aligned with school contexts and students’ needs; (3) information and communication technology skills-educational service area offices should provide hands-on training supported by mentoring or technology coaching; and (4) life and career skills-schools should promote performance agreements (PA) that emphasize meaningful professional development, supported by systematic supervision, monitoring, and individual consultation.